2010
DOI: 10.2967/jnumed.109.073130
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT Enterography in Crohn Disease: Correlation of Disease Activity on CT Enterography with 18F-FDG Uptake

Abstract: We combined 18 F-FDG PET and CT enterography in a single examination and compared the level of 18 F-FDG uptake measured by maximal standardized uptake value (SUVmax) with the CT enterography patterns of disease activity found in patients with Crohn disease (CD). Methods: Twenty-eight patients (mean age, 37.5 y; 11 male and 17 female) suspected of having active CD underwent PET/CT enterography. Abnormal bowel segments recognized on CT enterography were graded qualitatively for the presence of perienteric fat in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…13 Very recently, FDG-PET/CT has proven to be useful for both the diagnosis and follow-up of human IBD, although some concerns are raised on the high radiation exposure during these PET investigations. [14][15][16] Brewer et al 2 described the use of FDG-PET in various animal models of chronic colitis and showed that the cellular source of the increased FDG-signal in the setting of chronic intestinal inflammation is CD4 þ T cells. Acute DSS-colitis is highly lymphocyte-independent and principally mediated by neutrophils and, to a lesser degree, macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…13 Very recently, FDG-PET/CT has proven to be useful for both the diagnosis and follow-up of human IBD, although some concerns are raised on the high radiation exposure during these PET investigations. [14][15][16] Brewer et al 2 described the use of FDG-PET in various animal models of chronic colitis and showed that the cellular source of the increased FDG-signal in the setting of chronic intestinal inflammation is CD4 þ T cells. Acute DSS-colitis is highly lymphocyte-independent and principally mediated by neutrophils and, to a lesser degree, macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Groshar et al [93] showed a statistically significant difference in mean SUV max among the different mural patterns revealed on CT enterography: intramural edema (active inflammation), intramural soft tissue attenuation (inflammatory infiltrate), and intramural fat (chronic inflamma- tion). Therefore, PET-CT data could help to distinguish between acute inflammation and fibrotic strictures.…”
Section: Pet-ct Enterographymentioning
confidence: 98%
“…There is still limited evidence on these imaging methods both in adult and in pediatric IBO patients, but there is a good correlation between PET findings and disease activity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: General Remarks Andfuture Perspectivesmentioning
confidence: 99%